Dose reduction of scattered photons from concrete walls lined with lead: Implications for improvement in design of megavoltage radiation therapy facility mazes. Issue 2 (12th January 2015) - Al‐Affan, I. A. M.; Hugtenburg, R. P.; Bari, D. S.; Al‐Saleh, W. M.; Piliero, M.; Evans, S.; Al‐Hasan, M.; Al‐Zughul, B.; Al‐Kharouf, S.; Ghaith, A.
Abstract : Purpose: This study explores the possibility of using lead to cover part of the radiation therapy facility maze walls in order to absorb low energy photons and reduce the total dose at the maze entrance of radiation therapy rooms. Methods: Experiments and Monte Carlo simulations were utilized to establish the possibility of using high‐ Z materials to cover the concrete walls of the maze in order to reduce the dose of the scattered photons at the maze entrance. The dose of the backscattered photons from a concrete wall was measured for various scattering angles. The dose was also calculated by the FLUKA and EGSnrc Monte Carlo codes. The FLUKA code was also used to simulate an existing radiotherapy room to study the effect of multiple scattering when adding lead to cover the concrete walls of the maze. Monoenergetic photons were used to represent the main components of the x ray spectrum up to 10 MV. Results: It was observed that when the concrete wall was covered with just 2 mm of lead, the measured dose rate at all backscattering angles was reduced by 20% for photons of energy comparable to Co‐60 emissions and 70% for Cs‐137 emissions. The simulations with FLUKA and EGS showed that the reduction in the dose was potentially even higher when lead was added. One explanation for the reduction is the increased absorption of backscattered photons due to the photoelectric interaction in lead. The results also showed that adding 2 mm lead to the concrete walls and floor of the maze reduced the dose at the maze entrance by up to 90%. Conclusions: This novel proposal of covering part or the entire maze walls with a few millimeters of lead would have a direct implication for the design of radiation therapy facilities and would assist in upgrading the design of some mazes, especially those in facilities with limited space where the maze length cannot be extended to sufficiently reduce the dose.